Disordered eating in a population‐based sample of young adults during the COVID‐19 outbreak. Issue 7 (15th March 2021) - Simone, Melissa; Emery, Rebecca L.; Hazzard, Vivienne M.; Eisenberg, Marla E.; Larson, Nicole; Neumark‐Sztainer, Dianne
Abstract: Objective: The present study aimed to describe the experience of, and factors associated with, disordered eating in a population‐based sample of emerging adults during the COVID‐19 outbreak. Method: Participants in the EAT 2010–2018 (Eating and Activity over Time) study were invited to complete the C‐EAT (COVID‐19 EAT) survey in April–May 2020. There were 720 respondents to the survey (age: 24.7 ± 2.0 years). Psychological distress, stress, stress management, financial difficulties, and food insecurity during the COVID‐19 pandemic were examined as cross‐sectional correlates of disordered eating in 2020. Open‐ended questions assessed the perceived impact of the pandemic on eating behaviors. Results: Low stress management was significantly associated with a higher count of extreme unhealthy weight control behaviors (UWCBs). Food insecurity, higher depressive symptoms, and financial difficulties were significantly associated with a higher count of less extreme UWCBs. Higher stress and depressive symptoms were significantly associated with greater odds of binge eating. Six themes pertaining to disordered eating during the pandemic emerged: (a) mindless eating and snacking; (b) increased food consumption; (c) generalized decrease in appetite or dietary intake; (d) eating to cope; (e) pandemic‐related reductions in dietary intake; and (f) re‐emergence or marked increase in eating disorder symptoms. Discussion: Psychological distress, stress management, financial difficulties, and abrupt schedule changes may have contributed to disordered eating during the COVID‐19 pandemic. Interventions that target stress management, depressive symptoms, and financial strain and provide tools to develop a routine may be particularly effective for emerging adults at risk of developing disordered eating during public health crises.